Pengaruh Merokok terhadap Kejadian Karsinoma Sel Skuamosa Kulit: Evidence-based Case Report: Analisis - Faiqueen Dhia Salsabila Firlana Adnan; Edelyne Chelsea; Adhimukti Tathyahita Sampurna (Cermin Dunia Kedokteran, 2025)
Introduction: Cutaneous squamous cell carcinoma (SCC) is the second most prevalent skin cancer in the world. The correlation between smoking and cutaneous SCC is still inconclusive. Methods: Further investigation through literature search was conducted in 3 databases, which were PubMed, Scopus, and Cochrane. The investigators also conducted hand searching by examining references in each acquired article. Selection of articles is based on established inclusion and exclusion criteria. Critical appraisal used instruments from the Oxford Centre for Evidence-Based Medicine and the CASP checklist. Results: All four selected articles show that smokers have a higher risk of cutaneous SCC with OR 1.08 to 2.96. Conclusion: Smoking increases the risk of cutaneous SCC.